Traceless Synthesis of Asymmetrically Modified Bivalent Nucleosomes. Issue 8 (25th January 2016) - Lechner, Carolin C.; Agashe, Ninad D.; Fierz, Beat
Abstract: Nucleosomes carry extensive post‐translational modifications (PTMs), which results in complex modification patterns that are involved in epigenetic signaling. Although two copies of each histone coexist in a nucleosome, they may not carry the same PTMs and are often differently modified (asymmetric). In bivalent domains, a chromatin signature prevalent in embryonic stem cells (ESCs), namely H3 methylated at lysine 4 (H3K4me3), coexists with H3K27me3 in asymmetric nucleosomes. We report a general, modular, and traceless method for producing asymmetrically modified nucleosomes. We further show that in bivalent nucleosomes, H3K4me3 inhibits the activity of the H3K27‐specific lysine methyltransferase (KMT) polycomb repressive complex 2 (PRC2) solely on the same histone tail, whereas H3K27me3 stimulates PRC2 activity across tails, thereby partially overriding the H3K4me3‐mediated repressive effect. To maintain bivalent domains in ESCs, PRC2 activity must thus be locally restricted or reversed. Abstract : Make and break : A facile and traceless method to assemble asymmetric post‐translationally modified nucleosomes was developed. By using a cleavable peptide tag (the lnc‐tag), a library of asymmetric bivalent nucleosomes was generated, which allowed investigation of the intranucleosomal crosstalk between two modifications in the regulation of the histone methyltransferase PRC2.